1984
DOI: 10.1002/kin.550160109
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation reactions between alkyl and fluoroalkyl radicals. II. Fluoro‐ and trifluoromethyl with ethyl radicals

Abstract: Cross-disproportionation/combination ratios for CFH2 and CF3 with C2H5 radicals have been determined to be A = 0.032 f 0.012 and A = 0.098 f 0.020, respectively, over the temperature range 25-75°C. For the pathway that yields CFH and CzHs, A = 0.020 f 0.005 a t 25°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The donor radical contains a CF 3 group at the ␣-carbon and this electronrich substituent may repel an incoming CF 3 acceptor radical, but not a CF 3 CH 2 CHCH 3 radical that has a greater hydrocarbon-radical character. A similar trend has been observed by Pritchard and coworkers [16][17][18][19][20]. For example, when the donor radical was CHF 2 and the acceptor radical was changed from a perfluoro radical to an alkyl radical, k d /k c , for several acceptor radicals, varied as follows: 0.088 (CF 3 ), 0.072 (n-C 3 F 7 ), 0.07 (CHF 2 ), 0.06 (CH 2 F), 0.35 (CH 3 ), 0.37 (C 2 H 5 ), and 0.30 (n-C 3 H 7 ).…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…The donor radical contains a CF 3 group at the ␣-carbon and this electronrich substituent may repel an incoming CF 3 acceptor radical, but not a CF 3 CH 2 CHCH 3 radical that has a greater hydrocarbon-radical character. A similar trend has been observed by Pritchard and coworkers [16][17][18][19][20]. For example, when the donor radical was CHF 2 and the acceptor radical was changed from a perfluoro radical to an alkyl radical, k d /k c , for several acceptor radicals, varied as follows: 0.088 (CF 3 ), 0.072 (n-C 3 F 7 ), 0.07 (CHF 2 ), 0.06 (CH 2 F), 0.35 (CH 3 ), 0.37 (C 2 H 5 ), and 0.30 (n-C 3 H 7 ).…”
Section: Figuresupporting
confidence: 89%
“…Pritchard and coworkers [17] also found that hydrocarbon acceptor radicals have much larger k d /k c ratios than perfluorocarbon radicals. As mentioned previously, Pritchard and coworkers [16][17][18][19][20] found that methyl, ethyl, and n-propyl radicals, accepting an H from CHF 2 , all had k d /k c near 0.3, whereas the k d /k c values were between 0.06 and 0.09 when the acceptor radical was a n-C 3 F 7 or a CF 3 radical.…”
Section: Figurementioning
confidence: 66%
“…The data can be fit to a linear plot with an intercept of 0.066 ± 0.051. In principle the intercept should be the disproportionation-combination ratio ( k d / k c ) for reaction 2, which is reported to be 0.09 ± 0.01. A steady-state analysis of the rate equations shows that the slope of this plot should be equal to k H (1 + k d / k c ) + k d / k c ( k HF ).…”
Section: Experimental Rate Constantsmentioning
confidence: 99%
“…The following reactions summarize the principal chemical reactions in this photolytic system. The combination/ disproportionation ratio for CF 3 + CHF 2 is 0.09, 28 and the small amount of singlet-state :CF 2 will be removed by reaction with trans-2-butene. An asterisk denotes vibrational excitation of CF…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation